Assessement of competitiviness of Moldovan agri-food products at the regional level - Eugenia Lucasenco; Alexandru Ceban (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper aims to assess the competitiveness of Moldovan agri-food products at the regional level, with an emphasis on neighbouring countries. Taking into account the latest trends in export of agri-food products, it is becoming necessary to analyze what are the most competitive Moldovan products on the regional EU market. In order to carry out the proposed assessment, the Revealed Comparative Advantage index has been used. This index helps calculating the relative advantage or disadvantage of a specific country in a certain class of goods as evidenced by trade flows. As a result, products with a significant comparative advantage have been identified, meaning the existence of the competitive potential at the regional level. At the same time, several proposals have been formulated in order to increase the competitiveness' level of selected Moldovan agri-food products.
Keywords: Q17; 330; trade; Revealed Comparative Advantage index (RCA); Republic of Moldova; agri-food products